STRATEGY IN EFFORTS TO IMPROVE THE QUALITY OF SERVICE CUSTOMER SATISFACTION USERS ONLINE OJEK (GO-JEK) - Isyanto, Puji; Mulya Karnama, Maman; Yani, Dini; Handayani, Rini (International Journal of Psychosocial Rehabilitation, 2020)
PT Applications Karya Anak Bangsa (Go-Jek Indonesia) which is a technology company with a social mission to improve the welfare and livelihoods of workers in various informal sectors in Indonesia. Founded in 2010 as an online telephone service for motorcycle riding. The purpose of this research is to examine the Go-Jek service quality strategy on customer satisfaction of Go-Jek users. This research uses a quantitative descriptive research method with a qualitative approach. Qualitative research is used because the research procedures that produce descriptive data in the form of research data information that uses a natural setting, with the intention of interpreting the description of phenomena that occur and carried out by involving a variety of existing methods. The results of this study indicate that: (1) there is Go-Jek customer satisfaction in the dimensions of responsiveness, assurance, empathy, tangible while the reliability dimension was not found to be a significant difference because Go-Jek has adequate facilities (2) Factors affecting Go-Jek customer satisfaction is a facility that is provided in providing services, application systems that are easy to use, affordable prices, location determination, services provided, a variety of fantastic promo voucher packages that benefit users of Go-Jek services, speed in responding to every need and desire. The quality strategy on the service attributes provided has become an icon of attraction and pay attention to reliability and improve service quality in terms of time.